Advancing Workplace Civility: a systematic review and meta-analysis of definitions, measurements, and associated factors - Peng, Xue (Frontiers in Psychology, 2023)
This research article focuses on the significance of Workplace Civility, defined as the respectful and courteous behavior exhibited by individuals toward their colleagues in the workplace. The primary objective of this study is to conduct a systematic review and a meta-analysis that synthesizes existing research by: (1) identifying operational definitions of the construct, (2) underlying the strongest correlations with other variables, (3) summarizing the effective strategies for promoting Workplace Civility, and (4) highlighting gaps in the literature, using the theory-characteristics-context-methodology (TCCM) framework. Multiple databases were meticulously searched, yielding 691 results, and ultimately 51 documents were included in the systematic review final sample following the application of predefined exclusion criteria. Then, a meta-analysis has been conducted including those studies with sufficient statistical data (k = 24) which allowed us to calculate 45 Effect Sizes. The review findings expose a notable dearth of research on Workplace Civility when compared to studies on incivility. This dearth highlights the pressing need for additional research endeavors to precisely define Workplace Civility, establish a robust theoretical framework, and develop reliable scales for its measurement. Related to the desirable correlates, organizational commitment, job satisfaction and mental health showed a high ES value, and for undesirable correlates, intention to quit showed a high ES value, while Emotional exhaustion only reached a medium ES value and physical symptoms showed a low ES value. Importantly, this study emphasizes that fostering civility in the workplace can yield significant benefits such as improved physical and mental well-being for workers, reduced burnout, and absenteeism rates. Thus, the promotion of civility in the workplace not only leads to healthier organizations but also enhances cost-efficiency, effectively averting the loss of both human and economic capital.